PROFIL PENYIMPANAN OBAT DI INSTALASI FARMASI RUMAH SAKIT ANTAM POMALAA - Febryanti, Nafa (PHARMACY UMI JOURNAL SYSTEM, 2024)
ABSTRACT Drug storage is oneof the stages of management in pharmaceutical dosage forms to maintain drug quality, as well as to reduce the risk of loss and damage. A bad storage system can result in drugs being damaged and ineffective in treatment. The suitability of drug storage has been regulated in pharmaceutical standards in hospitals. This study aims to get an overview of the profile of drug storage in the pharmacy installation of Antam Pomalaa Hospital, Kolaka regency. This research is a descriptive study by collecting data from interviews and observations in the drug storage room at the pharmacy instllation of antam pomalaa hospital, kolaka regency. the research result have been calculated and analyzed using percentage analysis which result in facilities and infrastructure obtaining a conformity percentage of 84,2%. Compilation of drug stock in the storage warehouse obtains a conformity percentage og 83.3% and in recording drug stock cards obtains a conformity percentage of 100%. The total percentage is included in the good category according to the applicable conformity standards.